6G oriented blockchain based Internet of things data sharing and storage mechanism - Yu’na JIANG; Xiaohu GE; Yang YANG; Chengxiang WANG; Jie LI (Tongxin xuebao)
Considering the heterogeneity of various IoT system and the single point failure of centralized data-processing platform,a decentralized IoT data sharing and storage method based on blockchain technology was proposed.The block consensus and decentralized storage of shared data were realized through the PoS consensus mechanism.A block layered propagation mechanism between consensus node and verified node was proposed based on the Gossip protocol.The block propagation delay model and decentralization evaluation model of blockchain networks were derived.The trade-off between the block propagation delay and the decentralization degree of networks was analyzed.The simulation results demonstrate that the block propagation delay and degree of network decentralization decrease with the increase of minimal capabilities of consensus nodes.As an application example,in the trajectory data sharing scenario of confirmed patients,the data sharing smart contract is implemented and tested based on the Ethereum development platform.